Rendre la justice en Louisiane espagnole (1763-1803) : aménagements, improvisations et instrumentalisations - Soizic Croguennec (Caravelle)
Spanish Louisiana (1763-1803), including both eastern and western Floridas after 1783, is an exemplary cultural mosaic at the crossroads of empires. Examining daily justice is a way to shed light on this social mosaic while demonstrating how multiculturalism, multilinguism as well as the distance from the main centers of power have an impact on the working of the judicial system in this region.